Johann Georg Hamann: a source of resistance in times of absolutism of the Enlightened Reason - Hernández Pérez, Abraham (Logos. Anales del Seminario de Metafísica, 2018)
Johann Georg Hamann was the first critic of the Enlightenment and his first victim. His thought, enormously complex and articulated through some ideas well ahead of his time, was quickly covered with “irrationalism” by the hermeneutical incapacity of the enlightened circles of the moment, which subsequently resulted in a notorious disregard for his work by the History of Philosophy. The present article intends to show that the categories used at the time to define the thought of Hamann are inadequate. More specifically, it will attempt to show how the revision of the Enlightenment carried out by Hamann reflects an attitude of “radical enlightenment” and not of “irrationalism”.